Surface and sub-surface multi-proxy reconstruction of middle to late Holocene palaeoceanographic changes in Disko Bugt, West Greenland. (15th January 2016) - Moros, Matthias; Lloyd, Jeremy M.; Perner, Kerstin; Krawczyk, Diana; Blanz, Thomas; de Vernal, Anne; Ouellet-Bernier, Marie-Michele; Kuijpers, Antoon; Jennings, Anne E.; Witkowski, Andrzej; Schneider, Ralph; Jansen, Eystein
Abstract: We present new surface water proxy records of meltwater production (alkenone derived), relative sea surface temperature (diatom, alkenones) and sea ice (diatoms) changes from the Disko Bugt area off central West Greenland. We combine these new surface water reconstructions with published proxy records (benthic foraminifera - bottom water proxy; dinocyst assemblages – surface water proxy), along with atmospheric temperature from Greenland ice core and Greenland lake records. This multi-proxy approach allows us to reconstruct centennial scale middle to late Holocene palaeoenvironmental evolution of Disko Bugt and the Western Greenland coastal region with more detail than previously available. Combining surface and bottom water proxies identifies the coupling between ocean circulation (West Greenland Current conditions), the atmosphere and the Greenland Ice Sheet. Centennial to millennial scale changes in the wider North Atlantic region were accompanied by variations in the West Greenland Current (WGC). During periods of relatively warm WGC, increased surface air temperature over western Greenland led to ice sheet retreat and significant meltwater flux. In contrast, during periods of cold WGC, atmospheric cooling resulted in glacier advances. We also identify potential linkages between the palaeoceanography of the Disko Bugt region and key changes in the history of human occupation. Cooler oceanographic conditions at 3.5 ka BP support the view that the Saqqaq culture left Disko Bugt due to deteriorating climatic conditions. The cause of the disappearance of the Dorset culture is unclear, but the new data presented here indicate that it may be linked to a significant increase in meltwater flux, which caused cold and unstable coastal conditions at ca. 2 ka BP. The subsequent settlement of the Norse occurred at the same time as climatic amelioration during the Medieval Climate Anomaly and their disappearance may be related to harsher conditions at the beginning of the Little Ice Age. Highlights: Ocean temperature has a strong influence on ice sheet behaviour in West Greenland. Similar trends in Holocene ocean and Camp Century ice core temperature proxies. Oceanic conditions influenced the history of human occupation in West Greenland. Results from surface and sub-surface proxies agree when meltwater influence is low. Interpretation of surface water proxies complicated when meltwater influence is high.